First 2 steps are.
Divide both sides by 5280.
After that, square both sides.
Now show me some work..
I will then help some more.
I have an equation that calculates the distance between two coordinates on Earth. The problem is, I need to rewrite this equation to solve for a different variable.
D=Distance in feet
X=Person's longitude
Y=Person's latitude
A=Some place's longitude
B=Some place's latitude
D=5280*(SQRT( (69.1*(B-Y))^2 + (69.1*(A-X)*COS(Y/57.3)) ))
How can I rearrange this equation to solve for A not D?
Thanks
I'll raise you the next three steps (subtracting, dividing, then adding) if you check my work!
A = ( (((D/5280)^2)-((69.1*(B-Y))^2)) / 69.1*COS(Y/57.3) ) + X
I was really intimidated with this because of the giant square root sign, and the COS which I haven't used before. But once I did the first two steps, it just unraveled for me. I hope I did it right.